SOME MAIN ISSUES ASSOCIATED WITH CERTAIN TYPES OF ADMINISTRATIVE PROCEEDINGS - Avagyan, Norayr (State and Law, 2023)
The article "Some main issues associated with certain types of administrative proceedings" includes valuable opinions on important theoretical and practical issues regarding administrative proceedings. The author has emphasized that in order to improve the legal framework, it is first of all necessary to clearly define the need to balance the principles of the efficiency of administration and the protection of the rights and freedoms of individuals. As a result, the author came to the conclusion that:              1) the existence of separate types of administrative proceedings has a dual purpose. (1) ensuring the effectiveness of the implementation of public authority functions in individual spheres of administration, and (2) ensuring the guaranteed realization and protection of the rights and freedoms of individuals and legal entities participating in individual spheres of administration. The special structural or procedural rules of administrative proceedings in the legal system must fulfill the above two functions at the same time.              2) The legitimate purpose of providing for a specific type of administrative procedure and its features is the efficiency of administration in a specific area of public authority implementation and the improvement of structures for the protection of rights and freedoms of individuals, including ensuring the existence of an effective means of protection of rights in individual areas of administration.              3) It is the positive duty of the legal state to be guided by the concept that the principles of efficiency and legal protection of the person should be laid at the basis of the legal regulations, guaranteeing the realization of the latter with appropriate structures and procedures.              4) It is the positive duty of the competent body implementing a particular type of administrative procedure to reasonably balance the joint realization of the principles of administrative efficiency and legal protection of the person in the legal process.
Keywords: a separate type of administrative procedures; specialty; criteria; general principles; the efficiency of administration; balance of principles; human-centered theory